ANALISIS SOSIO KULTURAL PETANI NANAS (ANANAS COMOSUS) DI DESA TANJUNG BATU KABUPATEN OGAN ILIR - Aminullah (Jurnal Bakti Agribisnis, 2016)
The purpose of this research were to : (1) To determine the perception of farmers Pineapple (Ananas comosus) on farm Pineapple (Ananas comosus) at Tanjung Batu district of Tanjung Batu Ogan Ilir, (2) Determine how the analysis of the feasibility of farming Pineapple (Ananas comosus) The village of Tanjung Batu district of Tanjung Batu Ogan Ilir. This research was conducted in June 2015 by the survey. This study found that the perception of farmers on the availability of supporting infrastructure and facilities provided in order to smooth the absolute namely pineapple farm with a total score of 71 and a percentage of 61.74%, while for the farmer's perception that the experience was a factor of the success in pineapple farming is by total score 83 and a percentage of 72.17% for the farmer's perception that the extension is needed in the pineapple farm in the village of Tanjung Batu with a total score of 57 with a percentage of 49.57%, and the NPV value is Rp 12.10902 million, the IRR is equal to 29 , 03% and Net B / C of 1.13 then this shows that pineapple farming in the village of Tanjung Batu district of Tanjung Batu Ogan Ilir profitable and feasible (feasible) to be developed.